Computer simulation of the effect of an annular inclusion from a functionally graded material on the stress concentration around a circular hole in thin plates and cylindrical shells - Hart, E.L.; Terokhin, B.I. (Reports of the National Academy of Sciences of Ukraine, 2023)
Computer modelling and FEM analysis of the stress-strain state of thin plates and thin-walled cylindrical shells with a circular hole in the presence of a surrounding ring inclusion of a functionally graded material (FGM) is carried out. The influence of the dimensions of the FGM inclusion and the law of change of its elastic modulus on the concentration of the parameters of the stress-strain state of plates and shells in the vicinity of the hole is studied. The distribution fields of stress and strain intensities of plate-shell structural elements in the zones of local stress concentration are obtained. It has been established that when using an annular FGM inclusion with specific mechanical properties and geometric parameters, it is possible to reduce the stress concentration factor and the corresponding strain intensities in the vicinity of the hole by more than 35%. The law of change in the modulus of elasticity of the FGM inclusion and the width of the inclusion has a significant effect not only on the concentration of the parameters of the stress-strain state of the plate and shell but also on the nature of the stress distribution over their surfaces. The results of a series of large-scale computational experiments show that the use of an annular inclusion made of FGM makes it possible to reduce the intensity of both stresses and deformations around the hole, which opens up prospects for finding rational parameters of inclusions from the point of view of the maximum possible reduction in local stress concentration.